The Caregivers’ Perceptions Toward Self- Stigma and Quality of Life Among Individuals with Mental Illness in Sarawak - Rekaya, Vincent Balang; Saloma, Pawi; Shalin, Lee, Wan Fei; Merikan, Aren; Ong, Mei Fong; Razjesh, Robert Drahman (Asia Pacific Higher Learning Sdn Bhd, 2023)
Introduction: Stigma is a condition whereby a person adopts stigmatizing views widely held by the public, resulting in low self-esteem and a lack of hope. People with mental illness experienced a loss of control over life and diminished function, which caused them to be discriminated against and rejected, which led them to experience a poor quality of life. Objective: To explore self-stigma and its role in affecting the quality of life among individuals with mental illness in the community in Sarawak. Methods: The study utilized a generic qualitative descriptive approach that aimed to explore the perceptions among family members and caregivers towards stigma and quality of life among individuals with mental illness in the community. Purposive sampling was utilized. Twenty semi-structured interviews were conducted in the major divisions of Sarawak. Thematic analysis was used to identify categories and themes in respondents’ accounts of their perceptions related to their self-stigma and quality of life as individuals with mental illness in Sarawak. Results: Five main themes were constructed, namely: meager quality of life, poor sense of self-reliance, feelings of discrimination by the community, and inability to contribute and participate socially. These findings demonstrate that self-stigma does have a role and affects the quality of life of these individuals and their caregivers pessimistically. Conclusion: Hence, there is a dire need to incorporate non-governmental organizational active reduce participation and policy to establish positive mental health initiatives and social support to self-stigma and improve the quality of life of individuals with mental illness within Sarawak and in the global context.